Grit and Gratitude as Predictors of Flourishing In Post-Pandemic Students - Citra Ayu Kumala Sari; Dillia Nur Amalia; Dzakiyyah Fatmala (Universitas Muhammadiyah Surakarta, 2023)
The Covid-19 pandemic affected the level of individual flourishing, including students. However, research on flourishing with grit and gratitude as predictors still needs to be more explored. This study aims to determine the role of grit and gratitude towards flourishing in post-pandemic students. Voluntary convenience sampling was used to obtain respondents (N = 643 active students in the even semester 2021-2022). Data retrieval uses the grit scale, gratitude scale, and flourishing scale. Data analysis using multiple regression analysis obtained the result of the calculated F value of 490.061 with a significance value of 0.000 (p < 0.05). So, the variables grit and gratitude are predictors of flourishing variables. The effective contribution in the R Square column shows a figure of 0.605 or 60.5%. This means that the grit and gratitude variables contribute effectively to the flourishing intention variable by 60.5%. While other variables outside this study influenced the remaining 39.5%. They are partially showing that the most critical role in student flourishing in this study was grit (36.5%) compared to gratitude (24%). This study suggests that those who have higher levels of grit and gratitude will be able to maximize their abilities to obtain a quality and prosperous life, have positive emotions, and good study engagement.